Pertumbuhan dan Hasil Tanaman Meranti Pada Sistem Tebang Pilih Tanam Jalur : Growth and Yiels of Meranti in the Selective Cutting and Strip Planting System - Wahyudi Wahyudi; Antonius Triyadi; Firliyanty Firliyanty (JURNAL HUTAN TROPIKA, 2026)
Selective Cutting and Strip Planting (SCLP) silvicultural system can be applied in the logged over forest and low potential forest to improve their productivity . The research was aimed at creating the growth and yield modeling of Shorea plantations in the strip planting system. The research was conducted at research plots of SCLP in logged over forest of PT. Prabanugraha Technology, Central Kalimantan Province. The research plots were five plots of Shorea leprosula plantation that planted in 2008 (17 years old), 2013 (12 years old), 2022 (3 years old), 2023 (2 years old) and 2025 (5 months old) in which consisted of 200 samples of trees, respectively. Data of Shorea leprosula growth were analyzed using Stella 9.0.2 and SPSS 22, and predicted yield using table of volume, exponential, polynomial, and 5 sub models of polynomial equations. The research result showed that growth model of exponential equation was y= 1.0326.e0.013X (R2= 91.23%) with estimated cutting cycle at 35 years old, polynomial equation was y=0.03187x2 + 0.7991x + 0.4174 (R2= 82,63%) and estimated cutting cycle at 32 years old, and 5 sub models polynomial equations have R2> 95%) and estimated cutting cycle at 33 years old. The best model was 5 sub models polynomial equations that represented exponential equation and polynomial equation in the yield of volume